إشكالية تنويع الصادرات وأثرها على النمو الاقتصادي في الجزائر - حسين ،خولة; شلوفي، عمير (University of Eloued جامعة الوادي, 2025)
This study examines the relationship between export diversification and economic growth in Algeria over the period 1990–2023, using the Fourier Autoregressive Distributed Lag (FARDL) methodology, which allows the identification of both short- and long-run dynamic relationships while accounting for nonlinear structural fluctuations in the time series. Real Gross Domestic Product (GDP) is used as an indicator of economic growth, while total exports (EXPORT) serve as the main variable to measure the impact of export diversification. The results reveal the existence of a long-run equilibrium relationship between the two variables, indicating that an increase in exports leads to a rise in GDP. Although the effect is positive, it remains relatively weak and limited. The findings emphasize the need to strengthen export diversification policies beyond the hydrocarbon sector by developing manufacturing industries and high value-added services, as these measures contribute to achieving sustainable growth and reducing the vulnerability of the Algerian economy to oil price fluctuations.
The Issue of Export Diversification and Its Impact on Economic Growth in Algeria During the Period 1990–2023: An Empirical Study Using the Fourier Autoregressive Distributed Lag (FARDL) Approach
مقال
Keywords: تنويع صادرات; نمو اقتصادي; علاقة طويلة الأجل; تقلبات هيكلية; Export diversification; economic growth; Algeria; FARDL model; long-run relationship; structural fluctuations.